Text Message Reminders Increase Appointment Adherence in a Pediatric Clinic: A Randomized Controlled Trial - Chia-Lei Lin; Nila Mistry; Jordana Boneh; Hong Li; Rina Lazebnik (Hindawi Limited, 2016)
Background. High no-show rates can burden clinic productivity and affect patient care. Although multiple studies have shown that text messages improve appointment adherence, very little research has focused on low-income and predominantly African American populations in resident clinic settings. Objectives. To determine whether incorporating a text message reminder reduces the no-show rate at an urban, pediatric resident clinic. Methods. A randomized controlled trial was conducted at a tertiary level ambulatory pediatric practice between August 2014 and February 2015. Following a demographic survey, 170 patients were enrolled. Patients were randomized into control or intervention groups. All patients received the standard voice message appointment reminder, but the intervention group additionally received a text message reminder. The primary outcome was no-show rate. Results. 95.3% of the participants were African American, and the overall no-show rate was 30.8%. No-show rate was significantly lower in the intervention group (23.5%) than the control group (38.1%) representing a difference of 14.6% (p=0.04). No demographic factors were found to alter the association between no-show rate and text message intervention. Conclusions. Text message reminders effectively improve show rates at a resident pediatric practice with high no-show rates, representing a promising approach to improving appointment adherence.